Purification, Characterization and Kinetic Properties of Glucose 6-Phosphate Dehydrogenase from Polygonum cognatum Meissn Leaves - Demir, Hulya; Beydemir, Sukru; CIFTCI, Mehmet (Asian Journal of Chemistry, 2010)
In the present studies, the isolation, purification and kinetic properties of glucose-6-phosphate dehydrogenase (G6PD) in the Polygonum cognatum Meissn leaves were investigated. The purification procedure was composed of three steps viz., homogenate preparation, ammonium sulfate precipitation and DEAE-Sephadex A50 ion exchange chromatography. The enzyme, having the specific activity of 1.896 EU/mg proteins, was purified with a yield of 57.6 % and 124.08 fold at 4 ºC. Stable pH, optimum pH, optimum temperature, subunit molecular weight, native form molecular weight, Km and νmax values for NADP+ and glucose 6- phosphate (G6-P) substrates were also determined for the enzyme. Enzymatic activity was spectrophotometrically measured according to Beutler's method at 340 nm.